Diabetic retinopathy in type 1 diabetes patients in Western Norway. Issue 5 (25th January 2018) - Jansson, Ragnhild W.; Hufthammer, Karl Ove; Krohn, Jørgen
Abstract: Purpose: To describe the prevalence of diabetic retinopathy (DR), associated risk factors and health‐related quality of life (HRQoL) in a population‐based cohort of patients with type 1 diabetes mellitus (DM1). Methods: All patients underwent a general and ophthalmic examination including seven‐field stereo fundus photography for grading of DR and diabetic macular oedema (DMO). Kaplan‐Meier survival analyses were performed to evaluate disease progression in relation to diabetes duration, age and year of diabetes onset. HRQoL and its association with DR were assessed by the Medical Outcomes Study Short Form 36 (SF‐36) questionnaire. Results: A total of 237 DM1 patients were included. Mean age at inclusion was 34 years (range, 4–75 years), and mean diabetes duration was 19 years (range, 5 months–63 years). A total of 145 patients (61%) had DR. Sixty‐two patients (26%) had mild, 39 (16%) moderate and 13 (5%) severe nonproliferative DR, while 31 (13%) had proliferative DR. The prevalence of DMO was 8%. The most important risk factors predicting severity of DR were diabetes duration (p   <   0.0001) and HbA1c level (p   <   0.0001). Neuropathy (p   =   0.006), nephropathy (p   =   0.004) and male gender (p   =   0.02) were also significant predictors of DR. Compared to normative SF‐36 data, there was a linear trend of decreasing HRQoL with increasing severity of DR that was statistically significant for the four physical dimension scores. Conclusion: The prevalence of DR in DM1 was largely within the range of previous reports. Diabetes duration, HbA1c level, neuropathy, nephropathy and male gender were all significant predictors of DR severity. The patients with more severe DR had lower HRQoL.